Estudo de polimorfismo de DNA do gene codificador da LOXL-1 e prolapso de órgãos pélvicos em mulheres brasileiras - Silva, Carolina Landim Da Costa E [UNIFESP] (2019)
Introduction and hypothesis: We verified the presence of single nucleotide polymorphisms (SNP) rs2165241 of the lysyl oxidase-like 1 (LOXL-1) gene and the association with pelvic organ prolapse (POP) in Brazilian women and determined risk factors for POP development. Methods: We assessed 630 postmenopausal women divided into POP (stages III and IV) and control (stages 0 and I) groups by examination and peripheral blood sample collection. DNA sequence of interest was analyzed by real-time reverse-transcriptase polymerase chain reaction (RT-PCR). We used logistic regression models for the analysis, with p < 0.05 for significance. Results: There were no association between the polymorphism analyzed and POP. Multiple logistic regression analysis identified age [odds ratio (OR) = 1.09, confidence interval (CI) 95%= 1.07; 1.12], number of vaginal births (OR = 2.17, CI 95%= 1.67; 2.82), and family history (OR = 2.27, CI 95%= 1.41; 3.66) as independent risk factors for POP. Cesarean section was shown to be a protective factor (OR = 0.73, CI 95%= 0.56; 0.95). Conclusion: Our research suggests that there is a lack of association between DNA polymorphism rs2165241 of LOXL-1 with advanced POP in this population.